Hand-worn devices for assessment and rehabilitation of motor function and their potential use in BCI protocols: a review - Bates, Madison; Sunderam, Sridhar (Frontiers in Human Neuroscience, 2023)
Various neurological conditions can impair hand function. Affected individuals cannot fully participate in activities of daily living due to the lack of fine motor control. Neurorehabilitation emphasizes repetitive movement and subjective clinical assessments that require clinical experience to administer. Here, we perform a review of literature focused on the use of hand-worn devices for rehabilitation and assessment of hand function, with particular attention to protocols that involve brain-computer interfaces (BCIs). BCIs are gaining ground as a means of detecting volitional signals as the basis for interactive motor training protocols to augment recovery. All devices reviewed here either monitor, assist, stimulate or support hand and finger movement. A majority of studies reviewed here test or validate devices through clinical trials, especially for stroke. Even though sensor gloves are the most commonly employed type of device in this domain, they have certain limitations. Many such gloves use bend or inertial sensors to monitor the movement of individual digits, but few monitor both movement and applied pressure. The use of such devices in BCI protocols is also uncommon. We conclude that hand-worn devices that monitor both flexion and grip will benefit both clinical diagnostic assessment of function during treatment and closed-loop BCI protocols aimed at rehabilitation.